Physiological comparison of root trainer and polybag plants of Hevea brasiliensis - Sumesh, K.V.; Sonam, S.K.; Annamalainathan, K.; Jacob, James (Journal of Plantation Crops, 2015)
The physiology of root trainer plants in comparison to polybag plants of two popular Hevea clones, RRII 105 and RRII 430 was studied. Dry matter partitioning and physiological parameters like leaf water potential, relative water content, chlorophyll content, PS II activity and photosynthetic efficiency were studied in root trainer and polybag plants and compared. Root trainer plants had only 55 per cent less biomass than polybag plants at two whorled stage. No variation was noticed in water relations among the poly bag and root trainer plants. Total chlorophyll content and chlorophyll a/b ratio were higher in polybag plants than root trainer plants of both clones. Polybag plants showed higher light saturation point when gas exchange was measured at different photosynthetic photon flux densities. Though there was no variation in effective quantum yield (Φ PSII), the root trainer plants of RRII 105 showed more excess electrons (J*) at higher light intensities. Photosystem II activity and photosynthetic carbon assimilation rates were less in root trainer plants under open and shaded conditions. The results indicated that the root confinement in root trainer plants has significant effect on the physiology of plants. The reduction in plant biomass and other physiological traits in root trainer plants can be attributed to the limited space in the container, limiting further root growth, which otherwise is beneficial for giving a priming effect as long as the plant remains in the container. Further studies are needed to quantify this ‘stress factor’ in root trainer plants and its implications in growth and establishment of plants in the field.